ANALISIS DISIPLIN KERJA KARYAWAN PADA PT. KHARISMA DAYUNG UTARA PEKANBARU - Sri Indra Wahyuni; Ema Fitri Lubis (UIR Press, 2020)
This study aims to find out how the work discipline of the employees of PT. Kharisma Dayung Utara Pekanbaru. High workloads make employees undisciplined in their work. This research uses descriptive research that is looking for an overview of the research phenomena for later conclusions drawn. In this case the object to be investigated is employees who work at PT. Kharisma Dayung Utara Pekanbaru. The reason to use descriptive research type is because the variable studied is a single variable so it does not require testing hypotheses and statistics, only it gives an overview of how discipline in working for employees at PT. Kharisma Dayung Utara Pekanbaru. The method used in this research is census sampling with the same population and sample, namely 32 people. The results showed that the work discipline was in a good category based on 8 indicators, role models of leadership, remuneration, justic, respect, sanctiion and assertiveness obtainedan average of 78.64%. That means that the average employee in the company feels that the company’s goals are in line with the abilities of their employees, with a high level of discipline they should make amployees more productive than before.